AB0854 PERSPECTIVES OF WOMEN WITH EXPERIENCE OF A FRAGILITY FRACTURE IN EUROPE: ATTITUDES TOWARDS FUTURE FRACTURE RISK, OSTEOPOROSIS AND PHARMACOTHERAPY. (June 2019) - Chaine, Charles; Ray, Peter; Timoshanko, Jen
Abstract : Background: Fragility fractures (FF) are common in women >50 years (yrs), with 1 in 3 experiencing a fracture (Fx). 1 However, the cause of these Fx is poorly recognised and measures taken to prevent future Fx are often inadequate. Recent US patient (pt) survey data suggest that awareness of osteoporosis (OP) and its contribution to Fx risk, appreciation of the benefits of OP pharmacotherapy (Rx), and discussion about OP with healthcare professionals (HCPs) are limited. 2 Objectives: This study gained insight into the attitudes and experiences of post-FF women in Europe regarding future Fx risk management. Methods: Women ≥51 yrs from Germany (DE), Spain (ES), UK, France (FR) and Italy (IT) (EU5) with self-reported experience of a FF completed a 30–min online survey (AplusA; 13–20 Feb 2018). Data are reported for EU5 pts who had their first Fx at ≥50 yrs; pts whose first Fx was a hand/finger or ankle/foot/toe Fx were excluded. Results: 199 women participated (DE: 38; ES: 36; UK: 41; FR: 34; IT:50). The most commonly experienced Fx was of the lower arm/wrist (43%). 43% reported >1 Fx (any type). Most women discussed bone health with an HCP within 6 months (mo) (70%; 42% with a GP) and HCPs were their primary source of information on OP (85%). Around a third reported taking a DEXA test within 6 mo of their first FF (37%). Advice from HCPs to prevent Fx focused on calcium/vitamin D supplements (74%) and diet/exercise changes (54%); 46% were prescribed OP-Rx. After having a FF, around half worried about future Fx (51%) and 39% voiced concerns about their general health (Figure). A third of pts thought that OP had caused their Fx (33%), most were likely to attribute it to a fall (67%). Only 18% felt empowered to manage their bone health; 61% did not think OP-Rx reduces risk of Fx or were unsure. 97% had never joined a support group. Conclusion: These results indicate that pts discuss future Fx risk with an HCP soon after having a FF and are concerned about future Fx. However, low levels of DEXA testing and OP-Rx, and poor awareness of the link between OP and Fx risk remain. Better education to empower women at risk of FF is critical. Reference: [1] Hernlund E. Arch Osteoporos2013;8:136; 2. Boudreau D. J Am Geriatr Soc2017;65:1829–35. Acknowledgement: The study was funded by UCB Pharma and Amgen, conducted by AplusA, medical writing by Arianna Psichas, Costello Medical, UK Disclosure of Interests: Charles Chaine: None declared, Peter Ray: None declared, Jen Timoshanko Employee of: UCB Pharma